The Concept, Nature and Manifestations of Terrorism - Almatov Sanjar Zakirjonovich (Researchparks Publishing, 2022)
In this article, the concept, nature and manifestations of terrorism are opened with scientific foundations, and the experiences of foreign developed countries are also taken into account.